Analytical prediction of particle detachment from a flat surface by turbulent air flows - Tippayawong N. (2014)
Detachment of deposited particles in turbulent air flows has been theoretically investigated, based on a quasi-static, critical moment model. Micrometer and submicrometer particles were considered in this study. Forces, i.e. adhesion, gravitation, aerodynamic lift and drag, and moments of these forces acting on particles deposited to a surface were considered and calculated as a function of particle size, and particle/surface system. Critical velocities of air flows for particle detachment were determined, and compared with experimental results from literature. The analytical prediction and experimental data were found to be in reasonable agreement. Trends between the two were similar. The analytical solutions predicted that the effect of aerodynamic drag played an important role in removal of fine particles from the surface. Critical velocity was found to increase with a decrease in particle size.